Impact of uncertainty on the performance of banking issuer shares 2018-2022 - Purwanto, Purwanto; Akhmadi, Akhmadi (Trigin Publisher, 2024)
The aim of this research is to determine the effect of inflation and interest rates on stock prices with the profitability of banking sector companies as an intervening variable for the 2018-2022 period. The approach used in this research is a quantitative approach. The research sample includes 30 banking sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. This research data is secondary data and was analyzed using panel regression analysis techniques. The results of this research are that inflation can have a direct impact on profitability, but interest rates do not have a direct impact on profitability. In addition, profitability directly affects stock prices. However, inflation and stock prices do not directly affect stock prices. Profitability cannot offset the impact of inflation and interest rates on share prices